2009
DOI: 10.1080/14733140903031432
|View full text |Cite
|
Sign up to set email alerts
|

The Place2Be: Measuring the effectiveness of a primary school‐based therapeutic intervention in England and Scotland

Abstract: Aim: There is increasing awareness of the prevalence of mental health disorders in children in the UK, but research on the efficacy of interventions meeting this need is limited. This study assessed whether The Place2Be model of individual and group intervention has a positive influence on children's social and emotional wellbeing. Providing emotional and therapeutic support to school age children in England and Scotland, The Place2Be delivers school‐based therapeutic interventions to around 47,000 children in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 30 publications
4
21
1
Order By: Relevance
“…The significant reduction in SDQ Total scores and Peer problem subscale scores experienced by victims of bullying following their engagement with the school counselling intervention reported in this paper is also supported within the more general school counselling evaluation literature, which presents school counselling as an effective support intervention for young people coping with a range of life and school-related issues (Burnison, 2003;Cooper et al, 2010;Education and Training Inspectorate, 2005;Fox & Butler 2003. This is particularly evident in the results reported by Lee et al (2009) from evaluating the effectiveness of the Place2Be school counselling service in the United Kingdom, and the meta-analysis of noncontrolled school counselling evaluation studies across the United Kingdom reported by Cooper (2009). A systematic scoping review of the evidence on counselling and psychotherapy for children and young people (Pattison & Harris, 2006, p. 112) concluded that ''counselling is a positive, useful and effective intervention for children and young people across the full range of issues''.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The significant reduction in SDQ Total scores and Peer problem subscale scores experienced by victims of bullying following their engagement with the school counselling intervention reported in this paper is also supported within the more general school counselling evaluation literature, which presents school counselling as an effective support intervention for young people coping with a range of life and school-related issues (Burnison, 2003;Cooper et al, 2010;Education and Training Inspectorate, 2005;Fox & Butler 2003. This is particularly evident in the results reported by Lee et al (2009) from evaluating the effectiveness of the Place2Be school counselling service in the United Kingdom, and the meta-analysis of noncontrolled school counselling evaluation studies across the United Kingdom reported by Cooper (2009). A systematic scoping review of the evidence on counselling and psychotherapy for children and young people (Pattison & Harris, 2006, p. 112) concluded that ''counselling is a positive, useful and effective intervention for children and young people across the full range of issues''.…”
Section: Discussionsupporting
confidence: 61%
“…Bearing in mind these methodological limitations, a recent meta-analysis of non-controlled UK-based school counselling evaluation studies documented a mean weighted effect size of 0.81 from pre to post counselling. Lee, Tiley, and White (2009) also report effectiveness of the UK-based The Place2Be school counselling intervention (n 01,864) with enhanced emotional health and well-being reflected in SDQ scores post intervention compared with pre intervention.…”
Section: School Counselling * An Effective Support Intervention?mentioning
confidence: 95%
“…An evaluation of the Place2Be intervention demonstrated a significant reduction in teacher and parent-reported SDQ Total difficulties scores and improvement in prosocial scores (Lee, Tiley, & White, 2009). Kids Company works to counter the effects of developmental adversity and support vulnerable children.…”
Section: School-based Interventionsmentioning
confidence: 97%
“…An evidence base confirming the effectiveness of counselling in schools began to accumulate: Fox and Butler (2009) reported on the success of the National Society for Prevention of Cruelty to Children Schools Counselling Project, where before and after TEEN CORE questionnaires from 104 secondary pupils indicated fewer problems and/or less distress; the Place2Be reported the effectiveness of primary-based counselling, showing lower total difficulties, using the data from over 1800 Strengths and Difficulty questionnaires across England and Scotland (Lee, Tiley, & White, 2009). A comprehensive review of 30 audit and evaluation studies by Cooper (2009) found that counselling significantly reduced the psychological distress of young people.…”
Section: Literature Reviewmentioning
confidence: 98%